Rats' processing of visual scenes: effects of lesions to fornix, anterior thalamus, mamillary nuclei or the retrohippocampal region. - Gaffan, E; Bannerman, D; Warburton, E; Aggleton, J (2001)
We analysed the effects of lesions of hippocampal-diencephalic projections -- fornix (FX) mamillary bodies (MB) and anterior thalamic nuclei (AT) -- and retrohippocampal (RH) lesions including entorhinal cortex and ventral subiculum, upon scene processing. All lesions except FX were neurotoxic. Rats learned to discriminate among computer-generated visual displays ("scenes") each comprising three different shapes ("objects"). The paradigm was constant-negative; one constant scene (unrewarded) appeared on every trial together with a trial-unique variable scene (rewarded). Four types of variable scene were intermingled: (1) unfamiliar objects in different positions from those of the constant (type O+P), (2) unfamiliar objects in same positions as in the constant (type O), (3) same objects as the constant in different positions (type P), (4) same objects and positions as the constant but recombined (type X). Group RH performed like controls while groups FX, AT and MB showed (surprisingly) enhanced performance on types X and O. One explanation is that normal rats attempt to process all objects in a scene concurrently, while hippocampal-projection lesions disrupt this tendency, producing a narrower attention, which paradoxically aids performance with some variable types. The results confirm that the entorhinal cortex has a different function from other components of the hippocampal system.